Generation of potent cytotoxic T lymphocytes against in male patients with non-muscle invasive bladder cancer by dendritic cells loaded with dying T24 bladder cancer cells - Hwang,Eu Chang (2017)
ABSTRACT Background In order to induce a potent cytotoxic T lymphocyte (CTL) response in dendritic cell (DC)-based immunotherapy for bladder cancer, various tumor antigens can be loaded onto DCs. Objective The aim of this study was to establish a method of immunotherapy for male patients with non-muscle invasive bladder cancer (NMIBC), using bladder cancer-specific CTLs generated in vitro by DCs. Materials and Methods Monocyte-derived DCs from bladder cancer patients were induced to mature in a standard cytokine cocktail (IL-1β, TNF-α, IL-6, and PGE2: standard DCs, sDCs) or anα-type 1-polarized DC (αDC1) cocktail (IL-1β, TNF-α, IFN-α, IFN-γ, and polyinosinic:polycytidylic acid) and loaded with the UVB-irradiated bladder cancer cell line, T24. Antigen-loaded αDC1s were evaluated by morphological and functional assays, and the bladder cancer-specific CTL response was analyzed by cytotoxic assay. Results The αDC1s significantly increased the expression of several molecules pertaining to DC maturation, regardless of whether or not the αDC1s were loaded with tumor antigens, relative to sDCs. The αDC1s demonstrated increased production of interleukin-12 both during maturation and after subsequent stimulation with CD40L that was not significantly affected by loading with tumor antigens as compared to that of sDCs. Bladder cancer-specific CTLs targeting autologous bladder cancer cells were successfully induced by αDC1s loaded with dying T24 cells. Conclusion Autologous αDC1s loaded with an allogeneic bladder cancer cell line resulted in increased bladder cancer-specific CTL responses as compared to that with sDCs, and therefore, may provide a novel source of DC-based vaccines that canbe used in immunotherapy for male patients with NMIBC.